2011
DOI: 10.1007/s11740-011-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted asymmetric incremental sheet forming of titanium sheet metal parts

Abstract: Asymmetric Incremental Sheet Forming (AISF) is a relatively new manufacturing process. In AISF, a CNC driven forming tool imposes a localized plastic deformation as it moves along the contour of the desired part. Thus, the final shape is obtained by a sequence of localized plastic deformations. AISF is suitable for small series production of sheet metal parts as needed in aeronautical and medical applications. Two main process limits restrict the range of application of AISF in these fields. These are the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 4 publications
0
45
0
Order By: Relevance
“…The high working temperature may cause tool oxidation and tool wear [10,11] and this leads to lowered surface quality and scratches [5]. To reduce the tool temperature, tool oxidation and improve the sheet surface quality, three major approaches were employed in this work: 1) Employment of high temperature alloy: other than the steel, high temperature nickel alloy GH4169 was employed in the tool design and development.…”
Section: Development Of Hot Forming Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high working temperature may cause tool oxidation and tool wear [10,11] and this leads to lowered surface quality and scratches [5]. To reduce the tool temperature, tool oxidation and improve the sheet surface quality, three major approaches were employed in this work: 1) Employment of high temperature alloy: other than the steel, high temperature nickel alloy GH4169 was employed in the tool design and development.…”
Section: Development Of Hot Forming Toolsmentioning
confidence: 99%
“…Various methods of heat generation in ISF have been reported including by using hot air blowers [1], conduction with a forming chamber [2], radiation by a laser beam [3][4][5][6], friction through tool rotation [7][8][9] or Joule heat by DC current [10][11][12][13][14].These technologies greatly enhanced the ISF capabilities in fabrication of lightweight alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the forming behavior of Ti6Al4V sheets, deformation under elevated temperatures is needed. Therefore, multiple concepts for warm ISF processes were recently developed and introduced in the technical literature [9,10]. It was shown that, by using hot ISF process, the formability of lightweight alloys among them Ti-6Al-4V can be significantly improved [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In order to form e.g. titanium or magnesium alloys with a low formability at room temperature, heat-assisted ISF variants were developed, such as laser-assisted ISF by Duflou et al (2007) and Göttmann et al (2011), or ISF with resistance heating, see e.g. Göttmann et al (2012).…”
Section: Introduction To Incremental Sheet Metal Formingmentioning
confidence: 99%